A method for preparing samples by EBSD electrolytic polishing of medium / high entropy alloy spherical powder

By introducing the iron-based amorphous spherical powder framework and mechanical polishing liquid into the medium/high entropy alloy spherical powder, combined with hot pressing curing and electrolytic polishing, the problems of adhesive interference and low EBSD sample preparation efficiency are solved, and the preparation of high-quality EBSD samples is achieved.

CN119290935BActive Publication Date: 2025-03-18SHANDONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411832936.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the binder interference of medium/high entropy alloy spherical powder, resulting in the inability to directly obtain the grain orientation distribution results of independent powders, and the preparation of high-quality EBSD samples is inefficient and costly.

Method used

By introducing iron-based amorphous spherical powder as the peripheral framework of the spherical powder of the medium/high entropy alloy, and combining with the micro-etching effect of the mechanical polishing liquid, the adhesive interference on the calibration of the EBSD sample is removed, forming a sandwich structure for hot pressing and curing, and finally electrolytic polishing is performed to obtain a flat and smooth surface to be measured.

Benefits of technology

The interference of the binder on the calibration of spherical powder of medium/high entropy alloys is effectively removed, and the morphology of the powder is kept intact, and the grain orientation distribution results of independent powders are obtained, which solves the problem of difficulty in preparing EBSD samples. The method is simple and practical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290935B_ABST
    Figure CN119290935B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of EBSD sample preparation, and relates to a method for preparing a medium / high entropy alloy spherical powder by EBSD electrolytic polishing, comprising: mechanically mixing an iron-based amorphous spherical powder, a tin-bismuth alloy powder and a medium / high entropy alloy spherical powder to be tested to obtain a mixed powder; taking two metal plates with grooves, spreading the mixed powder in the groove of one metal plate, and then placing the other metal plate on the mixed powder to form a sandwich structure; after the sandwich structure is hot-pressed and solidified, a portion of one end of the metal plate located outside the groove is cut off to obtain a sample to be tested; one side of the cut metal plate is used as a surface to be tested, and after being polished and leveled, mechanical polishing and electrolytic polishing are performed to obtain the sample. The present invention can prepare medium / high entropy alloy spherical powder EBSD samples at low cost, high quality, large area, and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of EBSD sample preparation and relates to an EBSD electrolytic polishing sample preparation method for medium / high entropy alloy spherical powder. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] At present, medium / high entropy alloy spherical powder has been gradually widely used in the field of metal additive manufacturing and laser cladding. Obtaining high-quality powder EBSD (backscattered electron diffraction technology) samples is the key to improving the preparation technology of medium / high entropy alloy spherical powder.

[0004] There are two basic requirements for samples that meet EBSD testing: first, the surface to be tested must be flat and smooth; second, there must be no residual mechanical stress layer on the surface to be tested (mechanical stress layers are mostly introduced during crystal growth or mechanical polishing). However, the medium / high entropy alloy spherical powder used for additive manufacturing or laser cladding is small in size, and polishing and removing the stress layer are extremely difficult.

[0005] At present, most researchers use focused ion beam scanning electron microscope (FIB) to prepare EBSD samples of medium / high entropy alloy powder with good flatness and no residual mechanical stress layer. However, both gallium ion and argon ion equipment have the problems of expensive equipment and expensive sample preparation consumables, and low preparation efficiency. It is difficult to obtain large-area, high-quality EBSD samples at the same time, which has a certain impact on the process improvement of medium / high entropy alloy powder.

[0006] Patent CN201810846725.0 discloses a method for preparing an EBSD test sample of an iron-based alloy powder. However, in this method, the binder affects the calibration of the powder, and the grain orientation distribution result of the independent powder cannot be directly obtained. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a method for preparing samples by EBSD electrolytic polishing of medium / high entropy alloy spherical powder. The present invention introduces iron-based amorphous spherical powder as the outer skeleton of the medium / high entropy alloy spherical powder, and cooperates with the micro-etching effect of a mechanical polishing liquid to effectively remove the interference of a binder (tin-bismuth alloy) on the calibration of the medium / high entropy alloy spherical powder, maintains the integrity of the morphology of the medium / high entropy alloy spherical powder, obtains the grain orientation distribution result of the independent powder, and solves the problem of difficult EBSD sample preparation of medium / high entropy alloy spherical powder for metal additive manufacturing.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A first aspect of the present invention provides a method for preparing a sample by EBSD electrolytic polishing of medium / high entropy alloy spherical powder, comprising:

[0010] Mechanically mixing the iron-based amorphous spherical powder, the tin-bismuth alloy powder and the medium / high entropy alloy spherical powder to be tested to obtain a mixed powder;

[0011] Take two metal plates with grooves, spread the mixed powder in the groove of one metal plate, and then place another metal plate on the mixed powder to form a closed containing chamber, i.e., a sandwich structure;

[0012] After the sandwich structure is heat-pressed and solidified, a portion of one end of the metal plate located outside the groove is cut off to obtain a sample to be tested;

[0013] One side of the cut metal plate is used as the test surface. After grinding it flat, it is mechanically polished and electrolytically polished to obtain the test surface.

[0014] The iron-based amorphous spherical powder of the present invention mainly plays a role of skeleton support, not only has low cost, but also has similar electrolytic properties to medium / high entropy alloy powder, and will not affect the electrolytic polishing of medium / high entropy alloy. In addition, the iron-based amorphous powder belongs to amorphous materials and has no crystal structure, and will not interfere with the EBSD results of medium / high entropy alloy during the collection process. Therefore, preferably, the mass ratio of the iron-based amorphous spherical powder to the tin-bismuth alloy powder and the medium / high entropy alloy spherical powder is 0.8-1:1.1-1.3:1.8-2.

[0015] The medium / high entropy alloy spherical powder used in metal additive manufacturing or coaxial powder feeding laser cladding is relatively small, usually with a particle size of 15μm-105μm. In order to achieve a better mixing effect, the particle size of the iron-based amorphous spherical powder is studied in the present invention. The particle size of the iron-based amorphous spherical powder is 10μm-60μm, which can effectively reduce the contact area between the low melting point tin-bismuth alloy powder and the medium / high entropy alloy powder, and better achieve the dispersion of the high entropy alloy powder.

[0016] The tin-bismuth alloy powder has the characteristic of a low melting point and can be melted under hot pressing to achieve bonding with medium / high entropy alloy powder. In order to improve the fluidity of the tin-bismuth alloy powder and better bond the medium / high entropy alloy powder, the present invention studies its morphology and particle size. Preferably, the tin-bismuth alloy powder is a spherical powder with a particle size of 10 μm-35 μm.

[0017] Compared with the traditional hot pressing solidification, the present invention introduces a metal plate with grooves to form a sample block with a sandwich structure, which has the following advantages: (1) avoids the phenomenon that the powder is easily adhered to the pressure heads on both sides; (2) provides support and space for the flow of liquid tin-bismuth alloy; (3) provides rigid support and fixation for the mixed powder, which is convenient for later grinding, polishing and electrolytic polishing operations. Therefore, preferably, the thickness of the metal plate with grooves is 3.5mm-4mm, the length and width are both 8mm-10mm, and the depth of the middle groove is 1.2mm-1.8mm.

[0018] The present invention studies the pressure and temperature of hot pressing curing, and the results show that the pressure should not be too large to prevent the medium / high entropy alloy spherical powder to be tested from deforming after being pressed or introducing mechanical deformation stress on the surface. Therefore, preferably, the temperature of the hot pressing curing is 145°C-160°C, the holding time is 20min-25min, and the loading pressure is 40Pa-50Pa.

[0019] There are two purposes of mechanical polishing: first, to make the surface to be tested flat and smooth; second, to use an acidic solution to micro-etch the powder particles, especially the interface of the medium / high entropy alloy powder, to slightly corrode the tin-bismuth alloy around the medium / high entropy alloy spherical powder, to avoid the influence of the potential difference between the two during the electrolytic polishing process. However, the etching depth should not be too deep, about 400nm, to avoid insufficient bonding strength and spherical powder falling off. To this end, the present invention studies the composition of the polishing liquid. Preferably, the polishing liquid for mechanical polishing is composed of the following raw materials in weight percentage: 3%-5% magnesium oxide, 1.5%-3% citric acid, 1.5%-2.5% oxalic acid, and the rest is water.

[0020] In order to obtain the expected smoothness and micro-etching effect on the surface to be tested, the present invention studies the process conditions of polishing. Preferably, the polishing disk rotation speed of the mechanical polishing is 150r / min-200r / min, the polishing agent dripping rate is 20mL / min-25mL / min, and the polishing time is 4min-6min.

[0021] Electropolishing can make the metal surface achieve a very high smoothness through electrochemical leveling, thereby meeting the EBSD detection requirements. Therefore, the present invention studies the formula of the electropolishing polishing liquid. Preferably, the electropolishing polishing liquid is composed of the following raw materials in volume percentage: 5%-10% perchloric acid, 15%-20% 2-butoxyethanol, and the rest is anhydrous ethanol.

[0022] In order to achieve a better electrolytic polishing effect, the electrolytic polishing process needs to be adjusted based on factors such as the material to be processed and the composition of the polishing liquid. Therefore, the present invention studies the electrolytic polishing process. Preferably, the specific steps of the electrolytic polishing include: polishing for 10s-12s under the conditions of voltage 32V-38V, temperature 0℃-0.5℃, and rotation speed 100r / min-120r / min, followed by water washing and drying.

[0023] Beneficial Effects of the Invention

[0024] (1) The present invention uses electrolytic polishing to prepare EBSD samples of medium / high entropy alloy spherical powder. Electrolytic polishing can remove the stress layer with high efficiency and high quality. The entire processing process is not like vibration polishing or OPS (oxide) polishing, which easily leaves a few scratches and affects the accurate determination of powder grain boundaries or grain sizes. It can also make up for the shortcomings of FIB, which is time-consuming and costly.

[0025] (2) The spherical powder used in metal additive manufacturing or coaxial powder feeding laser cladding is relatively small in size, with a particle size of only 15μm-105μm. Electrolytic polishing has extremely high requirements for the conductivity of the material. Generally, only the conductivity of metal materials can meet the requirements of electrolytic polishing. In addition, before electrolytic polishing, the surface of the sample to be polished needs to be flat and smooth, which is also a relatively difficult task for powder samples. Therefore, in actual tests, no researcher has ever used electrolytic polishing to prepare EBSD samples of medium / high entropy alloys. The present invention introduces iron-based amorphous spherical powder as the outer skeleton of medium / high entropy alloy spherical powder, and then cooperates with the micro-etching effect of mechanical polishing liquid to effectively remove the interference of the binder (tin-bismuth alloy) on the calibration of medium / high entropy alloy spherical powder, maintains the integrity of the morphology of medium / high entropy alloy spherical powder, obtains the grain orientation distribution results of independent powder, and solves the problem of difficulty in preparing EBSD samples of medium / high entropy alloy spherical powder for metal additive manufacturing.

[0026] (3) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0028] Figure 1 This is a schematic diagram of the sandwich structure of the present invention;

[0029] Figure 2 This is a schematic diagram of the sandwich structure after cutting according to the present invention;

[0030] Figure 3 is a comparison diagram of diffraction bands of Example 1 of the present invention;

[0031] Figure 4 This is the IPF (anti-polar) orientation distribution diagram of Example 1 of the present invention;

[0032] Figure 5 This is an electron microscope image of Example 1 of the present invention;

[0033] Figure 6 is a surface distribution diagram of the element Fe (iron) in Example 1 of the present invention;

[0034] Figure 7 is a surface distribution diagram of the element Sn (tin) in Example 1 of the present invention;

[0035] Figure 8 is a comparison diagram of diffraction bands of Example 2 of the present invention;

[0036] Fig. 9 This is the IPF orientation distribution diagram of Example 2 of the present invention;

[0037] Fig.10 This is an electron microscope image of Example 2 of the present invention;

[0038] Fig.11 This is a comparison diagram of the diffraction bands of Comparative Example 1 of the present invention;

[0039] Fig.12 This is the IPF orientation distribution diagram of Comparative Example 1 of the present invention;

[0040] Fig.13 This is an electron microscope image of Comparative Example 1 of the present invention;

[0041] Fig.14 This is a comparison diagram of the diffraction bands of Comparative Example 2 of the present invention;

[0042] Fig.15 This is the IPF orientation distribution diagram of Comparative Example 2 of the present invention;

[0043] Fig.16 It is the electron microscope image of comparative example 2 of the present invention. DETAILED DESCRIPTION

[0044] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0045] Terminology explanation:

[0046] The "medium / high entropy alloy" of the present invention refers to: a medium / high entropy alloy with transition elements such as Fe, Co (cobalt), Ni (nickel), Cr (chromium), and Mn (manganese) as the main elements, for example: FeCoNiCrMn (iron cobalt nickel chromium manganese), FeCoNiCr (iron cobalt nickel chromium), CoCrNi (cobalt chromium nickel), etc.

[0047] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0048] In the following examples and comparative examples, the particle size of the iron-based amorphous spherical powder is 10 μm-60 μm.

[0049] Sn 42 Bi 58 The particle size of the spherical alloy powder is 10 μm-35 μm.

[0050] Example 1

[0051] (1) Powder mixing:

[0052] The iron-based amorphous spherical powder, Sn 42 Bi 58 The spherical alloy powder is mechanically mixed with the CoCrNi medium entropy alloy spherical powder to be tested. The mixing process uses a three-dimensional powder mixer to mix evenly. The mixing process is: speed 80r / min, time 6 hours, and after mixing, it is taken out for use. Among them, the iron-based amorphous spherical powder, Sn 42 Bi 58 The mass ratio of the spherical alloy powder to the CoCrNi medium entropy alloy spherical powder is 0.8:1.3:1.8.

[0053] (2) Hot pressing of mixed powder:

[0054] Take a copper plate with grooves, the thickness of the copper plate is 3.5mm, the length and width are both 8mm, and the depth of the middle groove is 1.2mm. Spread the mixed powder in the groove on one side of the copper plate, and then place another piece on the powder to form a sandwich structure with copper plates on both sides and powder in the middle. Then, use a hot press with uniform heating devices on both sides for hot pressing and curing, the temperature is 145℃, the holding time is 25min, and the loading pressure is 40Pa.

[0055] (3) Mechanical polishing and etching in acidic environment:

[0056] First, use the cutting machine to cut off the excess copper plate on one side. Figure 2 As shown, the surface to be tested is obtained;

[0057] Then, the surface to be tested was polished and leveled using 120#, 400#, 800#, and 1500# metallographic sandpapers in sequence. Then, a polishing liquid was prepared, and the composition of the polishing liquid included: magnesium oxide: 30g, citric acid: 30g, oxalic acid: 15g, and deionized water: 925g.

[0058] The polished surface to be tested was mechanically polished and etched using the prepared polishing liquid. The polishing parameters were as follows: polishing disc speed 150 r / min, polishing agent dripping rate 20 mL / min, and polishing time 6 min.

[0059] (4) Electrolytic polishing: The formula of the polishing liquid (in volume percentage): 5% perchloric acid, 20% 2-butoxyethanol, and the rest is anhydrous ethanol. Electrolytic parameters: voltage 32V, temperature 0℃. Stirring speed 100r / min, polishing time 12s. Then rinse the surface of the electrolytically polished sample with deionized water and quickly blow dry with an air gun at an air pressure of 0.2Mpa. Finally, use a hair dryer to dry the surface to be tested for later use.

[0060] The prepared samples were subjected to EBSD test, and the test results are as follows: Figure 3-Figure 5 As shown, from the EBSD results of a single spherical powder particle, it can be seen that the diffraction band comparison diagram of the CoCrNi medium entropy alloy spherical powder to be tested is clear, the electrolytic polishing effect of the center and edge of the entire powder is good, and the grain orientation distribution result of the independent powder is obtained.

[0061] Depend on Figure 6 It can be seen that iron is distributed as a skeleton around the periphery of the CoCrNi medium entropy alloy spherical powder. Figure 7 It can be seen that tin exists around the CoCrNi medium-entropy alloy spherical powder, but the binder (tin-bismuth alloy) has not been calibrated.

[0062] Example 2

[0063] (1) Powder mixing:

[0064] The iron-based amorphous spherical powder, the low melting point alloy powder and the CoCrNi medium entropy alloy spherical powder to be tested are mechanically mixed, and the mixing process uses a three-dimensional powder mixer to mix evenly. The mixing process: the speed is 100r / min, the time is 5 hours, and the mixture is taken out for use. Among them, the iron-based amorphous spherical powder, Sn 42 Bi 58 The mass ratio of the spherical alloy powder to the CoCrNi medium entropy alloy spherical powder is 1:1.1:2.

[0065] (2) Hot pressing of mixed powder:

[0066] Take a copper plate with grooves, the thickness of the copper plate is 4mm, the length and width are both 10mm, and the depth of the middle groove is 1.8mm. Spread the mixed powder in the groove on one side of the copper plate, and then place another piece on the powder to form a sandwich structure with copper plates on both sides and a powder layer in the middle.

[0067] Then, a hot press machine with uniform heating devices on both sides was used for hot pressing curing, with a temperature of 160° C., a heat preservation time of 20 min, and a loading pressure of 50 Pa.

[0068] (3) Mechanical polishing and etching in acidic environment:

[0069] First, use the cutting machine to cut off the excess copper plate on one side. Figure 2 As shown, the surface to be tested is obtained;

[0070] Then, the surface to be tested was polished and leveled using 120#, 400#, 800#, and 1500# metallographic sandpapers in sequence. Then, a polishing liquid was prepared, and the composition of the polishing liquid included: magnesium oxide: 50g, citric acid: 15g, oxalic acid: 25g, and deionized water: 910g.

[0071] The polished surface to be tested was mechanically polished and etched using the prepared polishing liquid. The polishing parameters were as follows: polishing disc speed: 200 r / min, polishing agent dripping rate 20 mL / min, and polishing time 4 min.

[0072] (4) Electrolytic polishing: The formula of the polishing liquid (in volume percentage): 10% perchloric acid, 15% 2-butoxyethanol, and the rest is anhydrous ethanol. Electrolytic parameters: voltage 38V, temperature 0.5℃. Stirring speed 120r / min, polishing time 10s. Then rinse the surface of the electrolytically polished sample with deionized water and quickly blow dry with an air gun at an air pressure of 0.4Mpa. Finally, use a hair dryer to dry the surface to be tested for later use.

[0073] The prepared samples were subjected to EBSD test, and the test results are as follows: Figure 8-Figure 10 As shown, from the EBSD results of multiple spherical powder particles, it can be seen that the diffraction band comparison diagram of the CoCrNi medium entropy alloy spherical powder to be tested is clear, the electrolytic polishing effect of the center and edge of the entire powder is good, and the grain orientation distribution result of the independent powder is obtained.

[0074] Comparative Example 1

[0075] The difference from Example 1 is that no iron-based amorphous spherical powder is added.

[0076] EBSD test results are as follows Figure 11-13As shown in the figure, when no iron-based amorphous spherical powder is added, a large amount of electrolysis products appear around the powder after electrolytic polishing, causing the quality of the powder edge to deteriorate, making it impossible to obtain a complete and high-quality spherical powder EBSD sample.

[0077] Comparative Example 2

[0078] The difference from Example 1 is that no polishing liquid is used for mechanical polishing and etching.

[0079] EBSD test results are as follows Figure 14-16 As shown, it can be seen that if polishing liquid is not used for mechanical polishing and etching, there will be more electrolytic products around the powder after electrolytic polishing, which will cause the quality of the powder edge to deteriorate and it will be impossible to obtain a complete and high-quality spherical powder EBSD sample.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing samples by EBSD electrolytic polishing of medium / high entropy alloy spherical powder, characterized in that: include: Mechanically mixing the iron-based amorphous spherical powder, the tin-bismuth alloy powder and the medium / high entropy alloy spherical powder to be tested to obtain a mixed powder; Take two metal plates with grooves, spread the mixed powder in the groove of one metal plate, and then place another metal plate on the mixed powder to form a closed containing chamber, i.e., a sandwich structure; After the sandwich structure is heat-pressed and solidified, a portion of one end of the metal plate located outside the groove is cut off to obtain a sample to be tested; One side of the cut metal plate is used as the test surface, which is polished flat, and then mechanically polished and electrolytically polished to obtain the test surface; The particle size of the iron-based amorphous spherical powder is 10 μm-60 μm; The polishing liquid for mechanical polishing is composed of the following raw materials in percentage by weight: 3%-5% magnesium oxide, 1.5%-3% citric acid, 1.5%-2.5% oxalic acid, and the remainder water; The electrolytic polishing liquid is composed of the following raw materials in volume percentage: 5%-10% perchloric acid, 15%-20% 2-butoxyethanol, and the remainder is anhydrous ethanol.

2. The method for preparing a sample by EBSD electrolytic polishing of medium / high entropy alloy spherical powder according to claim 1, characterized in that: The mass ratio of the iron-based amorphous spherical powder to the tin-bismuth alloy powder and the medium / high entropy alloy spherical powder is 0.8-1:1.1-1.3:1.8-2.

3. The method for preparing a sample by EBSD electrolytic polishing of medium / high entropy alloy spherical powder according to claim 1, characterized in that: The tin-bismuth alloy powder is spherical powder with a particle size of 10 μm-35 μm.

4. The method for preparing a sample by EBSD electrolytic polishing of medium / high entropy alloy spherical powder according to claim 1, characterized in that: The thickness of the metal plate with grooves is 3.5mm-4mm, the length and width are both 8mm-10mm, and the depth of the middle groove is 1.2mm-1.8mm.

5. The method for preparing a sample by EBSD electrolytic polishing of medium / high entropy alloy spherical powder according to claim 1, characterized in that: The temperature of the hot pressing curing is 145° C.-160° C., the heat preservation time is 20 min-25 min, and the loading pressure is 40 Pa-50 Pa.

6. The method for preparing a sample by EBSD electrolytic polishing of medium / high entropy alloy spherical powder according to claim 1, characterized in that: The polishing disc rotation speed of the mechanical polishing is 150r / min-200r / min, the dripping speed of the polishing agent is 20mL / min-25mL / min, and the polishing time is 4min-6min.

7. The method for preparing a sample by EBSD electrolytic polishing of medium / high entropy alloy spherical powder according to claim 1, characterized in that: The specific steps of the electrolytic polishing include: polishing for 10s-12s under the conditions of voltage 32V-38V, temperature 0°C-0.5°C, and rotation speed 100r / min-120r / min, followed by water washing and drying.

Citation Information

Patent Citations

  • Preparation method of iron-base alloy powder EBSD detection sample

    CN109030148A

  • Sample preparation method for electron back scattering diffraction analysis of powder superalloy

    CN106404477A

  • High strength and toughness wear-resistant high entropy copper alloy

    CN109338202A